Spaces and Power Lines: A discourse-theoretical analysis of negotiation processes in the course of the national power grid extension - Weber, Florian; Kühne, Olaf (Raumforschung und Raumordnung | Spatial Research and Planning, 2016)
With its phase-out of nuclear power generation and the expansion of renewably sourced energy, the German energy transition (“Energiewende”) has radically changed existing power supply structures, with wide geographical repercussions. One aspect of this is changes within the being national power grid. Existing networks are to be upgraded and new long-distance power-lines built. This creates resistance and conflict. Against this background, our article investigates from a discourse theory perspective how power grid extensions and possible opposition are communicatively constructed, and what argumentation patterns dominate the discussion. The analyses undertaken here are based on a methodological mix of quantitative-oriented and qualitative elements that facilitates both the differentiation of central issues and detailed examination of individual aspects. In sum, the underlying need for grid extension and the technology involved on the one hand, and issues of health, local economies, natural environment, landscape, and participation in the decision-making process on the other hand, form central fields of conflict to be negotiated at cognitive, emotional and aesthetic levels of discourse.
Keywords: Energy transition; Renewable energies; Power grid extension; Discourse theory; Power